SEMANTIC ANALYSIS OF LEXICAL AMBIGUITY IN ANIES BASWEDAN’S POLITICAL INTERVIEW - Nafsatuzzahra, Tazkia (JEdu: Journal of English Education, 2026)
Ambiguity in communication often leads to misunderstandings for listeners. This issue may arise from a single word carrying multiple meanings, two or more words that share identical pronunciation, and other similar phenomena. This study was conducted with the aim of analyzing the phenomenon of lexical ambiguity in the context of political interviews, focusing on statements expressed by Anies Baswedan when he was a guest on ABC News Australia in 2023. The method employed in this study is qualitative, while the theory adopted is Stephan Ullmann's theory. The results of the study show that polysemy (14 words), homonymy (6 words), homograph (2 words), and homophony (3 words) were found in the interview. Hence, this study successfully proves that ambiguity is also present in political discourse and plays an essential role as a communication strategy.
Keywords: Political Interview; Lexical Ambiguity; Semantic